Echocardiographic imaging and ventricular mechanics in pulsatile-flow LVAD pediatric patients: a systematic approach - Iacobelli, R.; Di Molfetta, A.; Amodeo, A. (Frontiers in Pediatrics, 2024)
Echocardiography plays a crucial role in determining the eligibility for left ventricular assist device (LVAD) placement in patients experiencing advanced heart failure (HF) and in monitoring patient care after the implantation procedure. Because of its unique nature, pediatric population and pulsatileflow LVADs used in pediatrics require specific skills so that pediatric echocardiographers must develop a systematic approach in order to image the patients pre and post LVAD implantation.Therefore, the purpose of this narrative review is to delineate a systematic echocardiographic approach for pediatric patients supported by pulsatile-flow LVADs.